Implementation of innovations in skill ecosystems : promoting and inhibiting factors in the Indian context - Regel, Julia [Verfasser]; Rajagopalan, Anjana [Verfasser]; Mukherji, Arnab [Verfasser]; Basu, Sankarshan [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2024)
“Being considered a driver of economic growth as well as social participation and inclusion, skill development and vocational education and training (VET) policies constitute possible solutions to present challenges and ongoing problems. Therefore, VET has been the distinct subject of attempts toward development and improvement over time. For more than two decades, VET reforms have been a specific focus of Indian educational governance. However, in the subcontinent, reform initiatives have only partially succeeded in terms of their successful and sustainable implementation. This paper investigates promoting and inhibiting factors for vocational education and training policy implementation in Indian skill ecosystems. Taking the example of bottom-up policy implementation in the form of the Mahatma Gandhi National Fellowship (MGNF) programme, factors that affect the VET policy initiative are identified, based on a combination of quantitative and qualitative methods. Through a comprehensive questionnaire administered to a sample of 63 graduates of the programme, their perceptions on key implementation challenges regarding the local policy context, stakeholder cooperation, and institutional as well as implementer capacity were identified. The findings point to areas of further focus for policymakers for the effective implementation of VET initiatives while at the same time adding theoretical contributions to understanding and evaluating VET initiatives.“ (authors’ abstract; BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; I 2.3.4 Asien; 370; Berufsbildungspolitik; Reform; Einflussfaktor; Bildungssteuerung; Kompetenzentwicklung; Indien